Integrated orofacial therapy in chronic rhinosinusitis management for children with sleep bruxism - Haryono Utomo (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2010)
Background: The prevalence of rhinosinusitis was 20% in ambulatory patients and was mostly affected by viral infections and allergy. If conservative treatments of rhinosinusitis failed, surgical procedure is an alternative choice. Previous case report revealed that the rhinosinusitis symptoms were successfully relieved by the